Huosiland - Hammer, Carl I. (Archaeopress, 2018)
This volume studies the landscape of western Bavaria in the early-medieval period, between about 750 and 850 AD. The title of the study derives from several indications that a noble genealogia, the Huosi, were particularly influential there during the period. Huosiland may be the best documented European landscape of this time.